A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia) - Teslenko, Valentina A. (Zootaxa, 2019)
Capnia khingana sp. n. (Plecoptera: Capniidae) is described as a new brachypterous species from the Lesser Khingan Range south of the Far East of Russia. Detailed descriptions and illustrations are provided for both sexes. According to the diagnostic characters of the male epiproct, C. khingana sp. n. may be tentatively assigned to the C. atra species group.